1980
DOI: 10.2136/sssaj1980.03615995004400020042x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Urea by Granules of Sulfur‐Coated Urea

Abstract: Urea diffuses through holes in the coatings of granules of sulfur‐coated urea (SCU) into the surrounding soil. The ability to predict the rate at which urea is released from SCU granules aids in matching the slow release characteristics of the fertilizer to specific climatic and soil conditions.When openings are small and the concentration of urea immediately outside each opening is very low, a two‐stage release pattern is proposed. During the initial stage, solid urea is dissolving and urea diffuses out of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…N was released more steadily from PCU than from SCU, indicating that PCU had better controlled release properties of N [ 57 , 58 , 59 ]. Other studies have shown that the N release profile of PCU in the soil could be inferred from the N released in water at 25 °C [ 44 , 60 ]. It has also been shown that SCU granules release urea in the soil faster than in solution [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…N was released more steadily from PCU than from SCU, indicating that PCU had better controlled release properties of N [ 57 , 58 , 59 ]. Other studies have shown that the N release profile of PCU in the soil could be inferred from the N released in water at 25 °C [ 44 , 60 ]. It has also been shown that SCU granules release urea in the soil faster than in solution [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research clearly shows that soil temperature usually has the greatest influence on N release from polymer-coated urea fertilizer (Christianson 1988;Gandeza, Shoji, and Yamada 1991;Huett and Gogel 2000;Oertli and Lunt 1962). Jarrell and Boersma (1980) reported the diffusion rate and solubility of sulfur-coated urea fertilizer increased as temperature increased. Results from our experiment also showed that soil temperature had the greatest influence on N release from ESN.…”
Section: Discussionmentioning
confidence: 99%
“…In later work, it was noted that use of the microbicide was often discontinued (Shirley and Meline, 1975). N release from SCU is affected by soil temperature, soil water content, microorganism activity, and coating characteristics (Jarrell and Boersma, 1980).…”
mentioning
confidence: 99%